ANALYSIS OF TYPICAL NETWORK ATTACKS ON AUTOMATED SYSTEMS OF INTERNAL AFFAIRS DEPARTMENTS - I. G. Drovnikova; Е. S. Ovchinnikova; V. V. Konobeevsky (Вестник Дагестанского государственного технического университета: Технические науки, 2020)
Abstract. Aim Important contemporary trends in the theory and functional practice of secure automated systems at informatisation facilities of internal affairs bodies include an increase in the number of threats realised through remote unauthorised access (network attacks) on confidential in-formation resources, as well as the increasing complexity of implementing mechanisms aimed at providing protection from such attacks. In order to increase the effectiveness of existing and prospective automated security systems at the informatisation facilities of internal affairs bodies, it is necessary to identify and analyse typical network attacks aimed at components and software comprising these systems.Method. The method for solving this problem consists in a comprehensive analysis of the process of implementing network attacks on automated systems when they are used in secure mode in the informatisation facilities of internal affairs bodies.Results. Based on the analysis of information held in the security threat database developed by the Russian Federal Service for Technical and Export Control (FSTEC), modern features and operations of secure automated systems on the informatisation facilities of bodies of internal affairs and the results of a survey of experts in the field of information protection of allocated in accordance with the classification typology, eight types of dan-gerous attacks on automated systems of the internal affairs bodies are described taking into account their sources, objects, effects and possible consequences of implementation.Conclusion. The presented results are of use in further studies to conduct a quantitative assessment of the danger of typical attacks and for developing a private model of actual attacks for a specific automated system, taking into account their functional features in secure mode operations at the informatisation facility of the internal affairs body.